Mitigation of random and deterministic noise in mixed signal systems with examples in frequency synthesizer systems - Burress, Thomas Weston (Kansas State University, 2012)
RF frequency synthesizer systems are prevalent in today’s electronics. In a synthesizer there is a sensitive analog oscillator that may be affected by two different types of noise. The first is random noise injection from active devices. This results in phase noise in the synthesizer’s spectrum. The second noise source is deterministic. A digital frequency divider with high-amplitude switching is an example of such a deterministic source. This noise enters the system through various forms of electric or magnetic field coupling and manifests itself as spurs or pulling. Both forms of noise can adversely affect system performance. We will first summarize methods for reducing noise. These already known steps have to do with layout techniques, device geometry, and general synthesizer topologies. Then we will show ways to isolate noisy interfering circuits from the sensitive analog systems. Finally, we present some considerations for reducing the effects of random noise. A power supply filter can improve the effects of deterministic noise such as undesired signals on the supply line. We show several ways to improve the rejection of high frequency supply noise (characterized by the power supply rejection ratio or PSRR) through the design of a voltage regulator. The emphasis is on new techniques for obtaining good PSRR at S-band frequencies and above. To validate the techniques, we designed a regulator in Peregrine Semiconductor’s .25µm ULTRA CMOS Silicon on Sapphire process. It produces a 2.5V output with an input ranging from 2.6V to 5V and has a maximum current sourcing of 70mA. The regulator’s low drop out performance is 60mV with no load and it achieves a power supply ripple reduction of 29.8 dB at 500 MHz. To address random noise in synthesizers, the thesis provides preliminary investigation of an oscillator topology change that has been proposed in the literature. This proposed change reduces the phase noise of the oscillator within the overall system. A differential cross-coupled design is the usual topology of choice, but it is not optimal for noise performance. We investigate current noise injection in the traditional design and present an updated design that uses a differential Colpitts oscillator as an alternative to classic cross-coupled designs.
Keywords: Noise; Regulator; VCO; Synthesizer; Band gap reference; Crosstalk; Electrical Engineering (0544)